Experimental study on tissue-engineered urethral graft for repairing urethral defects in a rabbit model - Jiang, Aodi; Tian, Yu; Sun, Chengyang; Lian, Ying; Zhai, Hongfeng (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveTissue engineering represents a promising alternative for managing severe urethral defects. This study aimed to construct a tissue-engineered urethral graft by combining autologous urethral mucosal epithelial cells with an acellular dermal matrix (ADM) and evaluate its efficacy in tubularized repair of long-segment urethral defects in rabbits.MethodsAutologous urethral mucosal epithelial cells were harvested and seeded onto ADM scaffolds to fabricate tissue-engineered grafts. Cell adhesion, proliferation, and viability on the scaffolds were assessed using scanning electron microscopy (SEM), CCK-8 assay, and histological analysis. Thirty-six rabbits were randomly divided into three groups (n = 12 per group): Group A (control), where defects were repaired by end-to-end anastomosis; Group B (ADM-only), where defects were repaired using a tubularized ADM graft; and Group C (cell–ADM composite), where defects were repaired using a tubularized cell-seeded ADM graft. Radiographic, gross, and histological evaluations were performed 12 weeks post-surgery.ResultsThe ADM scaffold demonstrated good biocompatibility. The incidence of postoperative complications was 100% in Group A, 66.67% in Group B, and 8.33% in Group C. Statistically significant differences were observed between Group A and Group B, as well as between Group B and Group C (P < 0.05). Urethroscopy, imaging, and histological examinations revealed superior regenerative outcomes in Group C compared to Group B.ConclusionThe tubularized urethral mucosal epithelial cell–ADM composite graft is a feasible and effective strategy for repairing long-segment urethral defects in rabbits, exhibiting significantly better outcomes than ADM alone. Thus, this tissue-engineered construct represents an ideal alternative for long-segment urethral reconstruction.